Nutrients dynamics in pineapple (Ananas comosus L.) planted peat soil under fluctuating water table / Nur Qursyna Boll Kassim - Boll Kassim, Nur Qursyna (Institute of Graduate Studies, UiTM, 2016)
Peat soil was renowned for its low nutrient availability which limits its potential for extensive agriculture use. Continuous shifting of aerobic and anaerobic condition due to fluctuating water table could lead to biogeochemical changes of the soil that could affect the cycling of nutrients in the peat system. Understanding such changes on the nutrient dynamics will help in the management and the agronomic practices of pineapple plantation on peat soil. This study assess the dynamics of N, P and K in peat soil under fluctuating water table using laboratory simulation and nutrient balance estimation approach. The effect of rainfall, fate of applied fertilizer and lime and the nature of peat were studied in relation to changes in N, P and K. In the study, Nitrogen continue to decrease together with available P and the exchangeable bases (K, Ca, Mg and Na) in pineapple-cultivated peat compared to undisturbed peat despite the application of fertilizer. This could indicate that the nutrients are heavily leached by the alternating water table or they are readily taken up by the growing pineapple crops or they are readily fixed by the acidic peat soil. Fertilizer requirement in this system is therefore high in order to cope with leaching, potential fixation and uptake activity. Very little NO3--N was detected in the NPK fertilized aerobic peat while the application of urea resulted in significant amount of NH4+-N found in both aerobic and anaerobic peat soil…